Graphene-based interlayer for high-performance lithium–sulfur batteries: A review - Yong Liu; Huijie Wei; Xiaoliang Zhai; Fei Wang; Xinyuan Ren; Yi Xiong; Osaka Akiyoshi; Kunming Pan; Fengzhang Ren; Shizhong Wei (Materials & Design, 2021)
Lithium–sulfur (LiS) batteries have been widely studied, and considered as one of the most promising energy storage systems, because of their superior theoretical energy density, non-toxicity, high abundance, and environmental friendliness. However, LiS batteries suffer from problems such as the electrical insulating characteristic of sulfur and unsatisfactorily long cycling life. As a superior type of carbon material, graphene have been intensively investigated as intermediate layers to overcome these problems because of its large surface area, good chemical stability, and excellent electrical conductivity. In this review, we summarize the recent application of graphene-based materials, including simple graphene and graphene-based nanocomposites, as modifying interlayers in LiS batteries. Furthermore, the strategies to enhance their electrochemical performance are summarized and discussed, for example, physical and chemical confinement. Finally, the limitation and challenges of graphene-based materials as interlayers for LiS batteries, as well as their prospects for future research, are proposed. We hope that this review will be helpful for scientists to design and fabricate high-performance LiS batteries based on graphene-based interlayers and boost their practical applications.